2012
DOI: 10.1159/000342025
|View full text |Cite
|
Sign up to set email alerts
|

Position Sense of the Hemiparetic and Non-Hemiparetic Ankle after Stroke: Is the Non-Hemiparetic Ankle also Affected?

Abstract: Background and Purpose: Researchers have shown an increased interest in proprioception deficits of the paretic side in hemiplegic patients. However, far too little attention has been paid to the proprioception sense of the non-hemiparetic side. The objective of this research was to determine whether the position sense of the ankles, especially of the non-paretic side, is affected in stroke patients. Methods: 20 inpatients with stroke and 10 healthy control subjects were evaluated using an isokinetic dynamomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
(31 reference statements)
1
6
0
2
Order By: Relevance
“…A recent survey of 145 people (mean 45 months post stroke) found 43% reported reduced sensation in the feet; the second most common foot problem after weakness [23]. Prevalence rates of somatosensory deficits range from 7-70% [21,24] of chronic stroke survivors, with such variability partly attributable to the somatosensory modality tested and the use of different often non-standardised assessments. Therefore, an understanding of the prevalence and distribution of lower limb deficits in different somatosensory modalities in the chronic phase poststroke is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of 145 people (mean 45 months post stroke) found 43% reported reduced sensation in the feet; the second most common foot problem after weakness [23]. Prevalence rates of somatosensory deficits range from 7-70% [21,24] of chronic stroke survivors, with such variability partly attributable to the somatosensory modality tested and the use of different often non-standardised assessments. Therefore, an understanding of the prevalence and distribution of lower limb deficits in different somatosensory modalities in the chronic phase poststroke is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Yalcın et al 39 reported that action awareness is lost on the patient's lost position sense in the ankle due to stroke and this negatively affected the ambulation. In the literature, the normal standard deviation is accepted as approximately 2.0 ± 1.5 for the ankle.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, one familiarization trial was conducted. During the test, participants were blindfolded to rule out visual cues and no communication was allowed [38, 39]. The dynamometer moved each subject’s upper extremity passively at a fixed rate of 2.0° per second from the starting position (0° of abduction or flexion) to the reference positions (30° and 60° of abduction and then 30° and 60° of flexion).…”
Section: Methodsmentioning
confidence: 99%